Peningkatan Minat Menggunakan Quick Response Code Indonesian Standart (QRIS) Sebagai Pendukung Bisnis Islami - Hanni, Nabilla Febrie; Pujiastuti, Yanti (Journal Of Islamic Economics And Finance, 2023)
The purpose of this study is to determine The Effect Of Perceived Usefulness, Perceived Ease Of Use And Perceived Risk On Interest In Using The Quick Response Code Indonesian Standard (QRIS) As A Non-Cash Payment Method. (Study on Generation Z in Batang City). This study uses a quantitative approach. The population in this study is the Z generation who live in the city of Batang and users of the QRIS (Quick Response Code Indonesian Standard) application. The sampling technique uses a non-probability sampling technique with the number of population in this study cannot be known with certainty. Data analysis techniques used instrument testing, classical assumption testing, multiple linear regression analysis, model accuracy testing and hypothesis testing with the SPPS Statistics 22 program. Based on the results of this study, perceptions of usefulness partially have a positive and significant effect on interest in using QRIS, perceived ease of use partially has a positive and significant effect on intention to use QRIS. Perceived risk partially has a negative and insignificant effect on intention to use QRIS.